Carbon nanotubes-gold nanohybrid as potent electrocatalyst for oxygen reduction in alkaline media. Issue 41 (6th October 2015) - Morozan, Adina; Donck, Simon; Artero, Vincent; Gravel, Edmond; Doris, Eric
Abstract : Reduction of molecular oxygen is efficiently catalyzed by a carbon nanotube-gold nanohybrid. Abstract : A carbon nanotube-gold nanohybrid was used as catalyst for the reduction of molecular oxygen in acidic and alkaline media, the relevant cathode reaction in fuel cells. In alkaline medium, the nanohybrid exhibits excellent activity with a dominant 4e − reduction of O2 and low overpotential requirement compared to previously reported nano-gold materials. This property is linked to its capability to efficiently mediate HO2 − dismutation.